Novel germline mutations and unclassified variants of BRCA1 and BRCA2 genes in Chinese women with familial breast/ovarian cancer. Issue 1 (December 2016) - Cao, Wen-Ming; Gao, Yun; Yang, Hong-Jian; Xie, Shang-Nao; Ding, Xiao-Wen; Pan, Zhi-Wen; Ye, Wei-Wu; Wang, Xiao-Jia
Abstract Background Germline mutations in theBRCA1 andBRCA2 genes greatly increase a woman's risk of developing breast and/or ovarian cancer. The prevalence and distribution of such mutations differ across races/ethnicities. Several studies have investigated Chinese women with high-risk breast cancer, but the full spectrum of the mutations in these two genes remains unclear. Methods In this study, 133 unrelated Chinese women with familial breast/ovarian cancer living in Zhejiang, eastern China, were enrolled between the years 2008 and 2014. The complete coding regions and exon-intron boundaries ofBRCA1 andBRCA2 were screened by PCR-sequencing assay. Haplotype analysis was performed to confirmBRCA1 andBRCA2 founder mutations. In silico predictions were performed to identify the non-synonymous amino acid changes that were likely to disrupt the functions ofBRCA1 andBRCA2 . Results A total of 23 deleterious mutations were detected in the two genes in 31 familial breast/ovarian cancer patients with a total mutation frequency of 23.3 % (31/133). The highest frequency of 50.0 % (8/16) was found in breast cancer patients with a history of ovarian cancer. The frequencies ofBRCA1 andBRCA2 mutations were 13.5 % (18/133) and 9.8 % (13/133), respectively. We identified five novel deleterious mutations (c.3295delC, c.3780_3781delAG, c.4063_4066delAATC, c.5161 > T and c.5173insA) inBRCA1 and seven (c.1-40delGA, c.4487delC, c.469_473delAAGTC, c.5495delC, c.6141T > A, c.6359C > G and c.7588C > T) inBRCA2, which accounted for 52.2 % (12/23) of the total mutations. Six recurrent mutations were found, including four (c.3780_3781delAG, c.5154G > A, c.5468-1del8 and c.5470_5477del8) inBRCA1 and two (c.3109C > T and c.5682C > G) inBRCA2 . Two recurrentBRCA1 mutations (c.5154G > A and c.5468-1del8) were identified as putative founder mutations. We also found 11 unclassified variants, and nine of these are novel. The possibility was that each of the non-synonymous amino acid changes would disrupt the function ofBRCA1 andBRCA2 varied according to the different algorithms used. Conclusions BRCA1 andBRCA2 mutations accounted for a considerable proportion of hereditary breast/ovarian cancer patients from eastern China and the spectrum of the mutations of these two genes exhibited some unique features. The twoBRCA1 putative founder mutations may provide a cost-effective option to screen Chinese population, while founder effects of the two mutations should be investigated in a lager sample size of patients.